A retrospective analysis of eleven cases of invasive rhino-orbito-cerebral mucormycosis presented with orbital apex syndrome initially. Issue 1 (December 2016) - Jiang, Nan; Zhao, Guiqiu; Yang, Shanshan; Lin, Jing; Hu, Liting; Che, Chengye; Wang, Qian; Xu, Qiang
Abstract Background Rhino-orbito-cerebral mucormycosis(ROCM) is an invasive fungal infection that usually occurs in immunocompromised patients and sometimes presents as orbital apex syndrome(OAS) initially. It is rapidly fatal without an early diagnosis and treatment. We report the cases of invasive ROCM presenting with OAS initially in order to raise the attention of clinicians. Methods We retrospectively investigated eleven cases of invasive ROCM presenting initially with OAS admitted between January 2006 and December 2013. We analyzed clinical features, results of laboratory and radiological examinations, nasal endoscopy, aggressive surgical excision and debridement, and medical management outcomes of each case. Results A total of eleven cases of invasive ROCM with OAS as an initial sign were presented. Mucormycosis was accompanied by type II diabetes mellitus in nine cases, renal transplant in one case, and injury caused by traffic accident in one case. Anterior rhinoscopy revealed palatine or nasal necrotic lesions in all patients, and transethmoidal optic nerve decompression was carried out in three patients at the same time. CT scan revealed rhino-orbital-cerebral involvement in every patient. All patients were given intravenous amphotericin B. Nine patients underwent surgical debridement of necrotic tissue. Three patients survived. Conclusions ROCM is a severe, emergent and fatal infection requiring multidisciplinary management. It may often present with OAS initially. For ophthalmologist, mucormycosis must be considered in immunocompromised patients presenting with OAS initially, and anterior rhinoscopy is imperative before hormonotherapy, even in the cases absent of ketoacidosis induced by diabetes mellitus.